The genetic basis of psoriasis - Liên, Nguyễn Thị Kim; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2016)
Psoriasis is a chronic dermatitis disease. Although the disease is not dangerous but it affects patients’s life in many aspects and involving a large number of people in the world. Besides that, psoriasis related to many other diseases such as metabolic disorder, diabetes, cardiovascular disease or can develop into servere arthritis and psoriasis arthritis leading to joint deformities. HLAC gene located on chromosome 6 (locus PSORS1) is known to have an important role in the susceptibility of disease. Besides, investigations showed that psoriasis is controlled by many loci and genes. By using traditional methods and genome wide association studies (GWAS) have been identified 13 loci and many genes involved of disease. However, the role of each locus and gene influence to the susceptibility of disease, presentation of disease, time onset and the links with other diseases have not yet been defined clearly. Among the relevant loci, the PSORS1 locus still considered the main influence on the susceptibility of disease. Noteworthy, the factors of age, gender and race have influences to the disease manifestation of different loci. The studies also provides evidences of the relation of proriasis and increasing risk cardiovascular, hypertension, diabetes and other diseases. So that, by understanding the genetic basis of the disease, the doctors and patients can get orientation in prevention, treatment and minimizing the impact of the disease. In this article, we give a clearer view of the genetic basis of psoriasis.